HR outsourcing success: does partnership quality variables matter? - Ee, Elaine; Halim, Hasliza Abdul; Ramayah, Thurasamy (Journal of Business Economics and Management, 2013)
Recently, increased attention has been paid to partnership quality in outsourcing strategy. However, research of partnership quality on the outsourcing of human resources (HR) is very limited. Therefore, this research aims at examining the relationship between partnership quality variables (business understanding, trust, commitment, communication and top management) and the success of HR outsourcing. The sample is obtained from a cross sectional survey and the sample studied are 96 manufacturing organizations in Penang, Malaysia. Results indicate that most of the organizations that outsourced HR functions were from electronic and electrical industry. The analyses also show that partnership quality variables such as trust, business understanding and communication have significant positive impact on HR outsourcing success. The study concluded that HR outsourcing as a competitive strategy in Malaysia is still relatively new and probably many of its potential benefits are not fully understood. Therefore, by understanding the relationship with the service providers, the organizations are able to achieve outsourcing success by identifying areas of expected benefits and improvements.